Danos de Helicoverpa armigera (Lepidoptera: noctuidae) na fase reprodutiva da soja - Stacke, Regis Felipe (2016)
ABSTRACT 1 - Economic injury level (EIL) studies using insects are essential to support pest management decisions. The objectives of this study were to characterize and quantify the damage of H. armigera on soybean reproductive stages. In the 2013/14 and 2014/15 growing season in Santa Maria, RS, Brazil, four experiments were conducted in two soybean phenological stages (R2 and R5.1), with H. armigera larvae densities. The treatments were: T1 - control (0 larvae/m²); T2 - 2 larvae/m²; T3 - 4 larvae/m²; T4 - 6 larvae/m² and T5 - 8 larvae/m². Plants were infested with third instar larvae for 15 days. After harvesting, total number of pods, number of damaged pods, seed numbers, number of damaged seeds, 100 seed weight, and soybean yield variables were assessed in the upper, middle and lower soybean third. H. armigera cause more injuries in the middle part of the plant, followed by the upper and lower third. The damages caused in R2 were less severe compared to infestation at R5.1 growth stage. At R2 growth stage, the plant tolerated and compensated injuries caused by lower densities H. armigera, unlike what occurred at the R5.1 stage. The results demonstrated yield reductions of 69.05 kg/ha/larvae/m² at R2 and 87 kg/ha/larvae/m² at R5.1 stage.